Answer: =90+2x+3 Step-by-step explanation: Let’s simplify step-by-step. 2 + 82 + 8 − ( −6 − 2x + 5 ) Distribute the Negative Sign: = 2 + 82 + 8 + − 1 ( − 6 − 2x + 5 ) = 2 + 82 + 8 + − 1( − 6 ) + − 1 ( −2x ) + ( − 1 ) ( 5 ) = 2 + 82 + 8 + 6 + 2x + − 5 Combine Like Terms: = 2 + 82 + 8 + 6 + 2x + −5 = ( 2 + 82 + 6 ) + ( 2x ) + ( 8 + − 5 ) = 90 + 2x + 3 Hope it helps Please mark me as the brainliest Thank you Reply

Answer:=90+2x+3

Step-by-step explanation:Let’s simplify step-by-step.

2 + 82 + 8 − ( −6 − 2x + 5 )

Distribute the Negative Sign:

= 2 + 82 + 8 + − 1 ( − 6 − 2x + 5 )

= 2 + 82 + 8 + − 1( − 6 ) + − 1 ( −2x ) + ( − 1 ) ( 5 )

= 2 + 82 + 8 + 6 + 2x + − 5

Combine Like Terms:

= 2 + 82 + 8 + 6 + 2x + −5

= ( 2 + 82 + 6 ) + ( 2x ) + ( 8 + − 5 )

= 90 + 2x + 3

Hope it helpsPlease mark me as the brainliestThank you